THE BASIC PECULIARITIES OF FOREIGN LANGUAGE TEACHING, MODERN APPROACHES AND MAIN INSTRUCTIONS - Khamrayeva Nafisabonu Iskandar qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: As we know, methods of teaching foreign languages have a great importance in the education system. Each subject has its own teaching psychology. In this article, modern psychological methods, approaches and instructions for teaching foreign languages are mentioned. Basic information about the essence of scientific research on foreign language learning and the psychological aspects of increasing the effectiveness of foreign language learning is presented.